Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien (Studi Kasus di Puskesmas Kecamatan Depati VII Kabupaten Kerinci) - Edia Satria (Universitas Batanghari, 2021)
This study aims to determine 1) The extent to which the influence of the service quality on patient satisfaction of Puskesmas Kecamatan Depati VII Kabupaten Kerinci? 2) The extent to which the influence of the service quality on patient satisfaction of Puskesmas Kecamatan Depati VII Kabupaten Kerinci either directly or indirectly ? The Population in this study is patient of Puskesmas Kecamatan VII Kabupaten Kerinci period of 2017 totaling 7622 patients. Furthermore, by using the formula slovin, then obtained sample size of 75 patients with sampling accidental sampling technique. Data analysis tool used is the analysis of the path at an alpha level of 0.05. Based on the results of the study showed that: service quality positive and significant effect on patient satisfaction. Both directly and indirectly the quality of service has a positive and significant effect on patient satisfaction.